(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
The indiscriminate use of Lambda Cyhalothrin (LC), one of the commonly used synthetic pyrethroids (SPs) insecticides in agriculture, has led to the contamination of different environments with potentially serious impacts on the health of humans and animals. This study investigated the presence of LC-degrading bacteria in cultivated soils. Bacteria were isolated from agricultural soil on mineral salt medium (MSM) using an enrichment technique. They were characterized and identified. Their growth in different concentrations (50 mg/L, 75 mg/L, 100 mg/L, and 125 mg/L) of LC was studied, Potential to degrade LC was assessed by the growth of the bacteria in a mineral salts medium containing LC as the sole carbon source over 14 days. Five bacteria able to grow in MSM with LC as the sole source of carbon and on nutrient agar enriched with 100mg/L of LC were isolated. Their growth (turbidity and viable counts of the bacterial cells) increased from the third day till the sixth day, after which it declined till the 14th day. The Lambda Cyhalothrin-degrading bacterial isolates (LCDB) were tentatively identified as Bacillus species, Klebsiella species, Pseudomonas species, and Lysinibacillusspecies. These results indicated that these bacterial isolates are potentially able to degrade LC and can be useful for the remediation of SPs-contaminated agricultural soils.